2004
DOI: 10.2337/diabetes.53.8.2137
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Near the Insulin-Degrading Enzyme (IDE) Gene Contribute to Variation in Plasma Insulin Levels

Abstract: Insulin-degrading enzyme (IDE) plays a principal role in the proteolysis of several peptides in addition to insulin and is encoded by IDE, which resides in a region of chromosome 10q that is linked to type 2 diabetes. Two recent studies presented genetic association data on IDE and type 2 diabetes (one positive and the other negative), but neither explored the fundamental question of whether polymorphism in IDE has a measurable influence on insulin levels in human populations. To address this possibility, 14 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
8
40
2
Order By: Relevance
“…Evidence for a putative influence of IDE on the pathogenesis of type 2 diabetes was confirmed in association studies in several independent human populations [15][16][17] and in a recently published meta-analysis [18].…”
Section: Introductionmentioning
confidence: 84%
“…Evidence for a putative influence of IDE on the pathogenesis of type 2 diabetes was confirmed in association studies in several independent human populations [15][16][17] and in a recently published meta-analysis [18].…”
Section: Introductionmentioning
confidence: 84%
“…Thus, we have recently shown that polymorphisms in the insulin-degrading enzyme gene are linked to increased BMI and insulin resistance in men but not in women [36]. Similarly, a Leu7Pro polymorphism in the gene for neuropeptide Y, related to regulation of satiety and body weight, was demonstrated to be associated with IGT and type 2 diabetes in men but not in women [37].…”
Section: Discussionmentioning
confidence: 99%
“…None of the markers were significantly associated with APOB levels in non-smokers. Having provided evidence of their potential independent effects, we used a diplotype strategy (Gu et al 2004) to test for interactions between the R219K and R1587K variants, focussing on the smoking population. This strategy allows testing of haplotype effects, and can expose hybrids (individuals with two unlike haplotypes) that may contribute to trait variance.…”
Section: Resultsmentioning
confidence: 99%